Lifetime wave overtopping assessment of coastal defences under changing environments. (26th June 2019) - Mehrabani, Mehrdad Bahari; Chen, Hua-Peng
Coastal defence structures become more vulnerable due to changing environments such as sea level rise caused by climate change, hence requiring accurate time-variant reliability analyses in order to provide optimum maintenance strategies. This paper presents a method for assessing wave overtopping risk of the coastal defences subjected to changing operation conditions. The joint probability of sea water level and wave height is used to assess future hydraulic conditions on the basis of the UK climate projections. Structural resistance degradation of coastal defences such as the crest level settlement of earth sea dykes is also considered in the process of risk analysis and failure probability evaluation. A case study of a typical earth sea dyke section affected by changing environments is used to demonstrate the effectiveness of the proposed method. The results show that the overtopping failure probability of the earth sea dykes will increase significantly due to changing environments, and appropriate maintenances are needed to reduce the risk of the wave overtopping failure.